"Nas terras remotas o diabo anda solto": degredo, inquisição e escravidão no mundo atlântico português (séculos XVI A XVIII) - Thaís Tanure de Oliveira Costa (2018)
The present research aims to study the degredo of enslaved and freedmen by the Inquisition in the portuguese atlantic world between the sixteenth and eighteenth centuries. The degredo was a penalty that removed the condemned from his place of domicile taking him to live in another region. We investigate the political and religious imaginary of the Modern Era, trying to understand in which ideas and principles this form of exclusion was based. Practiced by the Inquisition, the degredo sought the penance of the individual and the purification of the social space where the crime was committed. It lay long roots in Judeo-Christian rituals of exclusion and sacrifice. In the Modern Age, the degredo was prescribed for frontier towns and cities in Portugal, for galleys and for colonial spaces. Using as sources mainly inquisitorial processes, this work seeks to understand why people often coming from the colonial spaces were sent to the Kingdom itself. This apparent contradiction is analyzed jointly with another: the fact that an enslaved was degredado removed him from his master’s house, who remained without his labor, resulting in monetary damages for him. Covering the study of the juridical condition of the defendant who was enslaved in the Portuguese Ancien Regime, we discuss the economic impact that the masters who had their captives degredados were subject to. In addition, adopting the methodological proposal of the Atlantic History, we persecute the steps of these men and women in the Kingdom, in their places of penalty execution, taking into account their experiences as africans or descendants of africans. We analyze the daily life of modern Portugal, seeking to perceive the various aspects that permeated the experience and life of the degredados in the galleys - vessels or forced labor - and in the frontier places of the Kingdom, former places of criminal shelter, to where much of these people were sent. We seek, behind the lines of the inquisitorial processes, to listen to the voices of the degredados and degredadas, reflecting on the ways in which they sought their sustenance, what relations they established, as was, in short, the experience of the degredo in Portugal for these people.